A Chronoamperometric Differential Electrochemical Mass Spectroscopy Study on the Growth of Li2O2 and Its Effect on the Mechanism of Oxygen Reduction in Dimethylsulfoxide Based Electrolytes. (10th August 2017) - Bondue, C.J.; Reinsberg, P.; Baltruschat, H.
Abstract: We report on potential step experiments into the oxygen reduction region in combination with differential mass spectroscopy (DEMS) and the rotating ring disc electrode technique (RRDE). We can thus distinguish between the one electron reduction path leading to superoxide and the 2 electron process leading to lithium peroxide. The evolution of the mass spectroscopic response in the DEMS experiments and evolution of the current at the ring electrode discloses that the deposition of lithiumperoxide hampers the capacity of the electrode for the consecutive transition of two electrons. The latter is required to form Li2 O2 on a direct electrochemical pathway. Instead, superoxide becomes the main product of oxygen reduction. A proportionality between coverage with Li2 O2 and the share of oxygen reduced to superoxide is observed at platinum. The effect of the Li2 O2 -deposit is less severe at large overpotentials. However, completion of a single monolayer of Li2 O2 on platinum and two monolayers on gold inhibit further oxygen reduction. We suggest that growth of larger Li2 O2 structures observed by other authors is caused by a chemical rout to Li2 O2 via superoxide disproportionation. Experimental evidence for the latter reaction is provided. In addition, we observe a non-monotonic faradaic current transient typical for nucleation after steps to certain potentials at the gold electrode and ascribe this to the formation of 2D Li2 O2 . This implies that nuclei of Li2 O2 have to form before the solid phase can grow uninhibited. Evidently the involved surface energies cause a crystallisation overpotential and therefore impair the formation of solid Li2 O2 .